Synthesis of ultra small iron oxide and doped iron oxide nanostructures and their antimicrobial activities. Issue 1 (11th December 2019) - , Atul; Kumar, Manish; Sharma, Anjna; Maurya, Indresh Kumar; Thakur, Alpana; Kumar, Sunil
ABSTRACT: Nanostructures of iron oxide and doped iron oxide with cobalt (Co), nickel (Ni) and zinc (Zn) have been prepared by wet chemical methods using sodium dodecyl sulphate (SDS) as capping agent. X-ray diffraction (XRD) and high resolution transmission electron microscopy (HRTEM) results showed that the nanostructures were crystalline with average crystallite size around 20 nm. The scanning electron microscopy (SEM) and transmission electron microscopy (TEM) images confirmed the granular shape of the nanostructures with ultra small size. The doping was confirmed in the XRD patterns and was well supported by Fourier transform infrared spectroscopy (FTIR). Band gap for iron oxide nanoparticles was found to be 2.2 eV and on doping the band gap found to be increased up to 2.5 eV. Ultra violet-visible (UV–Vis) measurements and blue shift of the optical band gap compliments the ultra small size of nanostructures as suggested by XRD, SEM and TEM studies. Interestingly, few of the compounds showed promising antifungal activity and might be used for antifungal treatment against fungal infection in future.